Mcdonough, Hitler And Nazi Germany; Neville, The Holocaust - Saylor, Thomas (Teaching History: A Journal of Methods, 2002)
The National Socialist period in Germany (1933-45) is of central importance to any understanding of modem Germany-indeed, to twentieth-century Western and world history as a whole. The complex and diverse economic, social, and political aspects of these twelve years have occupied historians for decades and no doubt will continue to do so. Nevertheless, despite the central importance of the Nazi experience, until now instructors and undergraduate students of the period have had very few comprehensive, yet brief, one-volume studies that are appropriate for survey-level courses.